The Effect of Various High-Probability to Low-Probability Instruction Ratios During the Use of the High-Probability Instructional Sequence. Issue 5 (September 2019) - Ertel, Hallie; Wilder, David A.; Hodges, Ansley; Hurtado, LeAnn
The high-probability (high-p) instructional sequence, which involves the delivery of a series of high-p instructions immediately before delivery of a low-probability (low-p) instruction, is a commonly used procedure to increase compliance among children and individuals with intellectual disabilities. Although the modal ratio of high-p instructions to low-p instructions is 3:1, other ratios may be more effective. In the current study, we compared three ratios of high-p with low-p instructions (i.e., 1:1, 3:1, and 5:1) during use of the high-p instructional sequence to increase compliance among three children with autism. Results suggest that the high-p sequence was effective to increase compliance for two of three participants and that the 5:1 ratio was most effective overall, although differences among ratios were slight for some participants. Implications of these findings and directions for future research are discussed.